The significance and necessity of automating the selection of sensors and actuators - Kolbasa, O. R.; Sotnik, S. V. (ХНУРЕ, 2025)
The theses are dedicated to the significance and necessity of automating the process of selecting sensors and actuators in technical process automation systems. An overview of the main approaches to implementing automated component selection is provided, including modern software tools and intelligent systems. Examples of sensor and actuator manufacturers are presented. The advantages of the automated approach compared to manual selection are analyzed. Conclusions are drawn regarding the effectiveness of this approach and the prospects for the development of relevant technologies. Тези присвячені значенню та необхідності автоматизації процесу вибору сенсорів і виконавчих механізмів у системах автоматизації технічних процесів. Проведено огляд основних підходів до реалізації автоматизованого вибору компонентів, зокрема сучасних програмних засобів та інтелектуальних систем. Наведено приклади виробників сенсорів та виконавчих механізмів. Проаналізовано переваги автоматизованого підходу порівняно з ручним вибором. Зроблено висновки щодо ефективності такого підходу та перспектив розвитку відповідних технологій.
Значення та необхідність автоматизації вибору сенсорів і виконавчих механізмів
Keywords: automated sensor selection; expert systems; industrial automation; автоматизація вибору сенсорів; експертна система; промислова автоматика